Gaseous Pollutants in Particulate Matter Epidemiology: Confounders or Surrogates? - Sarnat, Jeremy A.; Schwartz, Joel; Catalano, Paul J.; Suh, Helen H. (Environmental health perspectives, 2001)
Air pollution epidemiologic studies use ambient pollutant concentrations as surrogates of personal exposure. Strong correlations among numerous ambient pollutant concentrations, however, have made it difficult to determine the relative contribution of each pollutant to a given health outcome and have led to criticism that health effect estimates for particulate matter may be biased due to confounding. In the current study we used data collected from a multipollutant exposure study conducted in Baltimore, Maryland, during both the summer and winter to address the potential for confounding further. Twenty-four-hour personal exposures and corresponding ambient concentrations to fine particulate matter ( PM2.5), ozone, nitrogen dioxide, sulfur dioxide, and carbon monoxide were measured for 56 subjects. Results from correlation and regression analyses showed that personal PM2.5and gaseous air pollutant exposures were generally not correlated, as only 9 of the 178 individual-specific pairwise correlations were significant. Similarly, ambient concentrations were not associated with their corresponding personal exposures for any of the pollutants, except for PM2.5, which had significant associations during both seasons (p < 0.0001). Ambient gaseous concentrations were, however, strongly associated with personal PM2.5exposures. The strongest associations were shown between ambient O3and personal PM2.5(p < 0.0001 during both seasons). These results indicate that ambient PM2.5concentrations are suitable surrogates for personal PM2.5exposures and that ambient gaseous concentrations are surrogates, as opposed to confounders, of PM2.5. These findings suggest that the use of multiple pollutant models in epidemiologic studies of PM2.5may not be suitable and that health effects attributed to the ambient gases may actually be a result of exposures to PM2.5.